Performance study and assessment of phase noise suppression by incoherent addition in a mode-locked fiber laser system - Xue, Jin (2013)
This paper investigates the effectiveness of phase noise suppression by incoherent addition in a passively mode-locked fiber laser. Incoherent addition is achieved by using an interferometer external to the mode-locked laser. Two different types of interferometers, Mach–Zehnder and ring, are investigated experimentally for different background phase noise levels. Measurements show that both types of interferometers can achieve good phase noise reduction for a background phase noise level above − 130 dBc/Hz. Effects of dispersion management and pulse train intensity ratio in the interferometers are also discussed. Multi-stage cascaded interferometers are proposed for supermode noise suppression of harmonically actively mode-locked lasers.